Study of epoxy/CNT nanocomposites prepared via dispersion in the hardener - Caio Enrico Pizzutto; Jaqueline Suave; Jonas Bertholdi; Sérgio Henrique Pezzin; Luiz Antonio Ferreira Coelho; Sandro Campos Amico (Materials Research, 2011)
In this study, carboxylated (SWCNT-c) and pristine (SWCNT) single-walled carbon nanotubes were randomly dispersed in a hardener prior to mixing it with an epoxy resin. The influence of several parameters on the dispersion process were investigated. The produced samples were characterized by infrared spectroscopy, differential scanning calorimetry, dilatometry, dynamic mechanical analysis, scanning electron microscopy and mechanical testing (tensile, flexural and microhardness). The results obtained with the nanocomposites with SWCNT-c suggested that the lowest time and amplitude of sonication improved the mechanical properties. The use of a solvent (acetone) was important to improve dispersion, ultimately increasing microhardness and Young's Modulus up to 32%. Nanocomposites with 0.25 wt. (%) SWCNT-c presented superior mechanical properties compared to those with 0.50 wt. (%) SWCNT. Two simple mathematical models (rule of mixtures and Halpin-Tsai) were used to predict Young's Modulus of the composites yielding results very close to the experimental ones.